Status Hukum Ruang Udara dan Ruang Bawah Tanah dalam Tata Ruang Indonesia: Kekosongan Norma di Era Urban Vertikal - Geta Ilham Adi Prasetyo; Desi Sukmawati; Ahmad Fahmi Yustirandi; Budi Salman Farizy; Ajie Sefi Al Carubani; Afif Hiba Maula; Mohammad Naufal Hariri (Sekolah Tinggi Pertanahan Nasional, 2026)
Urban development in Indonesia shows a tendency towards vertical use of space through the construction of multi-storey buildings, underground infrastructure, and the use of airspace for public and commercial purposes. This situation raises legal issues regarding the status of control and use of airspace and underground space, which to date have not been clearly regulated in the national land and spatial planning legal system. Law No. 5 of 1960 concerning Basic Agrarian Principles and Law No. 26 of 2007 concerning Spatial Planning still place vertical space as an accessory to surface land rights, without regulating vertical boundaries of rights and mechanisms for independent encumbrance of rights. This study aims to analyse the legal regulation of airspace and underground space in Indonesian legislation, identify normative gaps that cause legal uncertainty, and formulate directions for spatial and land use law reform. The research method used is normative legal research with a legislative, conceptual, and comparative law approach. The results of the study show that there is a normative gap regarding the legal status of vertical space as an object of rights, which has implications for weak legal certainty in urban infrastructure development. Therefore, this study recommends legal reform through the recognition of airspace and underground space as separate legal objects, the establishment of new property rights, and the application of a three-dimensional cadastral system to ensure legal certainty in the use of vertical space in Indonesia. Keywords: Airspace, Underground Space, Spatial Planning, Land Law, Normative Vacuum.